In vitro evaluation of Moringa oleifera gum for colon- specific drug delivery - Singhal, Anil Kumar; Jarald, Edwin E; Showkat, Ahmad; Daud, Anwar (International Journal of Pharmaceutical Investigation)
Background: Moringa gum obtained from stem of the plant Moringa oleifera Lam. belonging to family Moringaceae. Number of naturally occurring polysaccharides obtained from plant (guar gum, inulin), animal (chitosan, chondrotin sulphate), algal (alginates) or microbial (dextran) origin. Objective: The present study was evaluated Moringa oleifera gum as a carrier for colon specific drug delivery using in vitro drug release studies. Materials and Methods: Six formulations of curcumin were prepared using varying concentration of Moringa oleifera gum containing 50 mg curcumin by wet granulation method. Tablets were subjected for evaluation by studying the parameter like hardness, friability, drug content uniformity and in vitro drug release study. Hardness was found to be in the range of 5.5 to 7.3 kg/cm2, the percentage friability was in the range of 0.60 to 0.89%, and tablet showed 98.99% to 99.89% of the labeled amount of curcumin indicating uniformity in drug content. Results and Discussion: In vitro drug release study was performed using simulated stomach, intestinal and colonic fluid. The susceptibility of Moringa gum to colonic bacteria was also assessed using drug release study with rat caecal contents. 30% Moringa gum containing formulation (F-3) was shown better drug released that is 90.46%, at the end of 24 h of dissolution study in the presence of rat caecal contents in comparison to 40% Moringa gum containing formulation (F-4) that was 78.03%. Conclusion: The results illustrate the usefulness of Moringa olefera gum as a potential carrier for colon-specific drug delivery.
Keywords: Cancer; curcumin; rat caecal content